Ireland : Fourth Post-Program Monitoring Discussions-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This paper focuses on Ireland's 2015 Fourth Post-Program Monitoring Discussions. Ireland's economy continues to improve at a robust pace. Real GDP expanded by 7 percent year-over-year over the first three quarters of 2015, with investment providing the largest contribution to growth followed by private consumption. High frequency indicators suggest that the strong economic momentum continued into the last months of 2015. Exchequer data for December indicate that 2015 revenues significantly exceeded the initial budget profile, whereas spending recorded a modest increase, leading to a likely outperformance of IMF staff's estimate of the 2015 general government deficit.